The Analysis of the Relationship Between the Processes from Different Types of Service Companies and Organizational Performance. Evidence from Romania - Andreea BARBU; Gheorghe MILITARU; Georgiana MOICEANU (Communications of International Proceedings, 2020)
Organizational performance is one of the most approached topics in the last period, this concept being attractive to both scientific and economic worlds. Also, this concept is analyzed concerning a lot of dimensions, factors and other concepts, including organizational processes. The goal of this paper is to analyze the relationships between the processes of different types of service companies and organizational performance. For this paper, the authors developed a questionnaire that was applied to a group of employees from the Romanian service companies. Based on their responses and perceptions, there were highlighted the most important processes that can contribute to improving organizational performance and also the most important or unimportant processes for each analyzed type of company. This study is an exploratory one, with evidence from Romania.
Keywords: Organizational performance; service company performance; business process performance.